Printed Music as a Medium of International Representation for the Magnates of the Grand Duchy of Lithuania: A Case Study of Music Prints Dedicated to Jan Karol Chodkiewicz and Aleksander Chodkiewicz - Pister, Aleksandra (Lietuvos istorijos studijos, 2022)
The article deals with the collections of printed music dedicated to the distinguished nobles, statesmen and military commanders of the Grand Dutchy of Lithuania, brothers Jan Karol and Aleksander Chodkiewicz. These collections were printed in Venice in the beginning of the 17th century and dedicated to the Lithuanian magnates by Italian composers Giovanni Valentini and Giulio Osculati. However, it was not in their home country where composers became acquainted with the above-mentioned noblemen who had studied and travelled extensively in Italy but in the Polish-Lithuanian Commonwealth. In fact, both composers had served for certain periods of time as musicians in the Polish court chapel under Sigismund III Vasa. The said collections of motets are being examined here with an emphasis on publicity and international representation. The author notes that besides the reasonable expectations of both Italian composers to raise their public profiles, to publish and disseminate their work in Europe, these personal aspirations also resonated with the interests of other public figures. They both represent Sigismund III Vasa, King of Poland and Grand Duke of Lithuania, as a generous patron and a leading social figure. The dedications were intended to glorify the Chodkiewicz and raise their profile within the Polish-Lithuanian Commonwealth and beyond. They account for the magnates’ victories in major military campaigns of the time, such as those achieved during the Polish–Swedish war of 1600–1611, as well as Chodkiewicz’s merits in defence of the state. Within the context of shifting confessional identities at the turn of the 16th and 17th centuries (i.e. the Reformation and the Counter-Reformation movements) these notated sources should be considered as a reflection of the magnates’ confessional identity. The very genre of printed works – motets for Catholic church service – reflects Chodkiewicz’s firm self-determination as Roman Catholics.
Keywords: Jan Karol Chodkiewicz; Aleksander Chodkiewicz; printed music; international representation; publicity; confessional identity; Giovanni Valentini; Giulio Osculati; Sigismund III Vasa